PENGEMBANGAN PARIWISATA HALAL DI INDONESIA TINJAUAN ETIKA BISNIS ISLAM - Alvien Septian Haerisma (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2018)
Abstract Halal industry becomes a global trend and business opportunities in various countries. Halal industry brings benefits to the Indonesian economy in terms of products. The scope of the halal industry in the midst of today's global economy includes several aspects: Financial services industry, food and beverage industry, pharmaceutical and pharmaceutical industry, cosmetic beauty industry, hospitals and tourism industry, and fashion and lifestyle industries. Halal tourism market becomes the future of a nation's economic resources. The demand for world halal tourism shows positive growth so that all countries in the world must prepare their infrastructure and become business opportunity as foreign exchange of the country. Economic activity is time to incorporate ethical values in various business branches. There are five key axioms governing Islamic business ethics in it consisting of unity, balance and equilibrium, free will, and responsibility and benevolence. Islamic business ethics in the development of halal tourism in Indonesia has been done by the government, businessmen or managers of tourism or the wider community as consumers and other stakeholders. Keywords: Halal Industry, Halal Tourism, and Islamic Business Ethics. Abstrak Industri halal menjadi tren global dan peluang bisnis diberbagai negara. Industri halal membawa kemanfaatan bagi perekonomian Indonesia dilihat dari sisi produk. Ruang lingkup industri halal di tengah perekonomian global saat ini mencangkup beberapa aspek, diantaranya: Industri pelayanan keuangan, industri makanan dan minuman, industri farmasi dan obat-obatan, industri kecantikan kosmetik, industri rumah sakit dan pariwisata, dan industri fashion dan lifestyles. Pasar pariwisata halal menjadi masa depan sumber ekonomi suatu bangsa. Permintaan pariwisata halal dunia menunjukkan pertumbuhan positif sehingga seluruh negara belahan dunia harus menyiapkan infrastrukturnya dan menjadi peluang bisnis sebagai devisa negara tersebut. Aktivitas ekonomi sudah saatnya untuk memasukkan nilai-nilai etik diberbagai cabang bisnis. Terdapat lima aksioma kunci mengatur etika bisnis Islami didalamnya terdiri: kesatuan (unity), keseimbangan dan kesejajaran (equilibrium), kehendak bebas (free will), dan tanggungjawab (responsibility) dan kebajikan (benevolence). Etika bisnis Islam dalam pengembangan pariwisata halal di Indonesia sudah dilakukan oleh pemerintah, pengusaha atau pengelola pariwisata atau juga masyarakat luas sebagai konsumen dan stakeholder lainnya. Kata Kunci: Industri Halal, Pariwisata Halal, dan Etika Bisnis Islam.